Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Step-by-step explanation:
[tex]x + y + z = 35 \\ x = y - 3 \\ z = 4y + 2 \\ \\ (y - 3) + y + (4y + 2) = 35 \\ 6y - 1 = 35 \\ 6y = 36 \\ y = \frac{36}{6} \\ y = 6 \\ \\ x = y - 3 \\ x = 6 - 3 \\ x = 3 \\ \\ z= 4y + 2 \\ z= (4 \times 6) + 2 \\ z = 26[/tex]
Answer:
the first number is 3
the second number is 6
and the third number is 26
Step-by-step explanation:
when you add 3, 6, and 26, you get a total of 35
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.